EFEKTIVITAS PENGELOLAAN LIMBAH PADAT MEDIS INFEKSIUS DI RUMAH SAKIT XYZ KOTA BALIKPAPAN - Sari, Iin Pratama; Hardiyono, Hardiyono; Kurniawati, Rati Cahyu (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Hospital XYZ of Balikpapan City, built-in 1949 by an oil company from the Netherlands established over a land area of 35,577.28 m₂. XYZ Hospital has 19 outpatient rooms, 17 inpatient rooms (150 beds), and several other facilities. This research used descriptive qualitative research with the number of respondents 5 people, the consideration used to determine the sample in this research is cleaning service officer (separation, packing, and transportation of infectious waste), medical waste burner (storage and burning of infectious solid waste) and head of HSE XYZ Hospital Balikpapan, this is done because the three parts are very closely related to infectious solid waste in the hospital. The results of field, observations showed a positive response to researchers in conducting field observations relating to the effectiveness of handling infectious solid waste in hospital XYZ. Based on research in the hospital there are conditions of waste management (segregation, packaging, storage, and standard of TPS building) 89% according to the rules and 11% are not in accordance with the rules, because there is an accumulation of B3 waste in TPS waste infectious waste, and for research hospital incinerator condition XYZ there are 80% suitable conditions and 20% unsuitable conditions, ie were not reaching the temperature at the maximum condition that is 1000 ° C which combustion only at condition 300 - 400 ° C which causes the condition of infectious waste not to ashes. Keywords: Infection, Solid Waste, Waste Management